P477 The efficacy of adalimumab for the treatment of Korean patients with ulcerative colitis and predictors of response: Preliminary results. (16th January 2018) - Choi, C H; Park, S J; Im, J P; Kim, H J; Lee, K -M; Kim, J W; Jung, S -A; Lee, J; Kang, S B; Shin, S J; Kim, E S; Kim, Y S; et al.
Abstract: Background: Data on effectiveness of adalimumab in Asian populations are lacking. We evaluated the efficacy and safety of adalimumab, and predictors of response in Korean patients with ulcerative colitis (UC). Methods: We conducted a prospective observational multicentre study over 56 weeks. Subjects initiated on adalimumab as per label for moderately to severely active UC were enrolled consecutively. Clinical response and remission were assessed by Mayo score. Mucosal healing was defined as Mayo subscore 0 or 1. Faecal calprotectin levels (mg/kg) were assessed at baseline, 8 and 56 weeks [CALPROLAB calprotectin ELISA (ALP)]. Serum adalimumab level (μg/ml) was measured at 8 weeks. We report the pre-planned interim analysis at Week 24. Results: A total of 146 patients with UC were enrolled. One hundred and thirty-one and 114 subjects were evaluable at 8 and 24 weeks, respectively. Clinical response rates at 8 and 24 weeks were 85.5% and 71.1%. Response rates were not different between patients naive or experienced to anti-TNF [86.0 vs. 83.9% at 8 weeks ( P = 0.769) and 73.3 vs. 62.5% at 24 weeks ( P = 0.298)]. Clinical remission rates at 8 and 24 weeks were 34.5% and 29.7%. Mucosal healing rate at 8 weeks was 57.1%. Patients with rectal bleeding score 0 increased from 5.3% at baseline to 51.3% at Week 8 and 66.7% at Week 24 (as observed). Adalimumab was dose escalated to 40 mg weekly in 24 (18.3%) patients. Mean CRP dropped from 4.3 ± 11.2 at baseline to 1.1 ± 2.2 at Week 8. Median faecal calprotectin dropped from 865.4 (IQR 308.2–1387.5) at baseline to 183.7 at Week 8 (IQR 73.7–721.7). Mean faecal calprotectin levels at 8 weeks was 270.3 ± 339.3 in patients with mucosal healing vs. 620.2 ± 572.5 without ( p = 0.002). Adalimumab drug levels were similar between responders and non-responders at 8 weeks (9.5 ± 5.1 vs. 9.7 ± 5.4). No clinical or laboratory parameters were associated with clinical responses at 8 and 24 weeks. Adverse events and serious adverse drug reactions were observed in four (2.7%) and one (0.7%). Conclusions: Adalimumab is effective in inducing clinical response, and mucosal healing in Korean UC patients. Faecal calprotectin is significantly lower in patients with mucosal healing. Primary non-response to adalimumab in UC is unrelated with drug level. There are no significant baseline predictors of response to adalimumab.